The People of the Book in the Qur'ān - Albayrak, Ismail (Islamic Studies, 2008)
The Qur'ān's understanding by Muslims has shaped their communal interfaith perceptions. This article selects the various Qur'ānic verses that have influenced Muslims in relating to people of faiths other than their own. The prime concern of this paper is to show how even the Qur'ānic verses that might sound harsh to the ears of other faith groups can be read with sensitivity and understanding in the modern world. To accomplish this, the article provides an historical analysis of the relevant Qur'ānic verses together with some current discussions on the issue. The Qur'ān, speaking generally, seems more germane to cultural and social plurality than to theological pluralism or dogmatic syncretism. In addition, the Qur'ān considers doing good — or competing in doing good — as vital in the life of people of different faith groups. Nonetheless, the Qur'ān accepts the People of the Book as they are and does not close the door to their exercise of religious freedom.